The need for ethical quality of life practices - Van Niekerk, Attie (Nederduitse Gereformeerde Teologiese Tydskrif, 2014)
This article reflects on ways in which the idea of an ethical quality of life of the people of God can be contextualized. This idea is largely similar to the concept of the wholeness of life that is found in documents of the World Council of Churches. Attention is given to the results of efforts to improve the quality of life in Africa through modernization during the development era, as well as to the quality of life in post-apartheid South Africa. The consumer culture has a strong influence on rich and poor, but there are different forms of resistance to modernisation. These forms of resistance often become destructive. If the church wants to present an attractive life-giving alternative, we need a moral vision, even a new cosmology, as well as the technology, practices, life styles and other ways to make that vision a reality.